Efforts to Handle Conflict in Madrasah - Imam Muhayat (Tarbiyah Departement collaboration with AMCA, 2022)
The purpose of this study is to explain in overcoming conflict in madrasas. The method used in this research is qualitative. The learning technique used is the study of the movement of the study room. The final result of the study confirms that there are several indicators of conflict that develop in madrasas. Conflict assets come from the different values and goals that develop from each agency and are not directed at communication. The forms or efforts to resolve conflicts that occur within the organization include: determining goals in overcoming organizational conflicts. Conflict control is achieved through mediators in getting closer to conflict actors and the use of accommodation methods. The effects of conflict can foster high-five college jobs even though many non-publics are now no longer helping college progress.